Australasian ACPGBI risk prediction model for 30-day mortality after colorectal cancer surgery. Issue 6 (28th September 2020) - Wilkins, S; Oliva, K; Chowdhury, E; Ruggiero, B; Bennett, A; Andrews, E J; Dent, O; Chapuis, P; Platell, C; Reid, C M; McMurrick, P J
Abstract: Background: Postoperative mortality after colorectal cancer surgery varies across hospitals and countries. The aim of this study was to test the Association of Coloproctologists of Great Britain and Ireland (ACPGBI) models as predictors of 30-day mortality in an Australian cohort. Methods: Data from patients who underwent surgery in six hospitals between 1996 and 2015 (CRC data set) were reviewed to test ACPGBI models, and patients from 79 hospitals in the Bi-National Colorectal Cancer Audit between 2007 and 2016 (BCCA data set) were analysed to validate model performance. Recalibrated models based on ACPGBI risk models were developed, tested and validated on a data set of Australasian patients. Results: Of 18 752 patients observed during the study, 6727 (CRC data set) and 3814 (BCCA data set) were analysed. The 30-day mortality rate was 1·1 and 3·5 per cent in the CRC and BCCA data sets respectively. Both the original and revised ACPGBI models overestimated 30-day mortality for the CRC data set (observed to expected (O/E) ratio 0·17 and 0·21 respectively). Their ability to correctly predict mortality risk was poor ( P < 0·001, Hosmer–Lemeshow test); however, the area under the curve for both models was 0·88 (95 per cent c.i. 0·85 to 0·92) showing good discriminatory power to classify 30-day mortality. The recalibrated original model performed well for calibration and discrimination, whereas the recalibrated revised model performed well for discrimination but not for calibration. Risk prediction was good for both recalibrated models. On external validation using the BCCA data set, the recalibrated models underestimated mortality risk (O/E ratio 3·06 and 2·98 respectively), whereas both original and revised ACPGBI models overestimated the risk (O/E ratio 0·48 and 0·69). All models showed similar good discrimination. Conclusion: The original and revised ACPGBI models overpredicted risk of 30-day mortality. The new Australasian calibrated ACPGBI model needs to be tested further in clinical practice. Graphical Abstract: The aim was to test the Association of Coloproctologists of Great Britain and Ireland (ACPGBI) original (2003) and revised (2010) models as predictors of 30-day mortality in an Australian patient cohort, and then recalibrate these models using data from Australian patients. This study included 10 541 patients treated over a 20-year interval in Australia and New Zealand. The ACPGBI models overestimated 30-day mortality, and so both ACPGBI models should be used with caution in Australia. Mortality risk prediction after colorectal surgery